FAKTOR RISIKO STUNTING PADA BALITA - Winarni Hamzah; Haniarti Haniarti; Rini Anggraeny (LPPM STIKES Muhammadiyah Kendal, 2021)
Stunting is one of the nutritional problems experienced by toddlers in the world today. In 2017, 22.2% of children under five in the world were stunted. Indonesia is included in the third country with the highest prevalence in the Southeast Asia region, the prevalence of children under five with stunting in Indonesia in 2005-2017 was 36.4%. Aims to determine the risk factors for stunting in children under five in the working area of ​​the Baraka Community Health Center, Enrekang Regency. This study used the analytical survey method with the Cross Sectional Study approach using the simple random sampling technique, which means that the sample taken is where each element or member of the population has the same opportunity to be selected as the sample. The sample size in this study was taken using the Slovin formula. The location was carried out in the working area of ​​the Baraka Community Health Center, Enrekang Regency. The research time was 1 month. The sample in this study amounted to 94 people with the process of data collection and data collection was carried out by interview techniques. The results showed that exclusive breastfeeding (p = 0.002), complementary breastfeeding (p = 0.002) had a relationship with the incidence of stunting, while there was no relationship between LBW (p = 0.106), gestational age (p = 0.303), and maternal nutritional status ( KEK) (p = 0.229) with the incidence of stunting.